O privilégio do clube fundador e a boa gestão nas SAD's - Lourenço, Raquel da Paz (2018)
This essay aims to analyse the Capital Companies in Sports legal system, focusing on the set of laws that rules the Corporate Governance. As legally binding, despite the default norm of Corporative Law’s, we currently have in Portugal Lei n. º 10/2013, from January 25th, and Lei n. º 5/2007, from January 16th. The constitution of these companies may follow one out of three mechanisms, being one of them the solely format that defends the Club, granting it a privileged position relatively to the remaining shareholders. This approach gives the club the right to elect at least one of the administrators to compose the board of directors of the company. This project will question whether both the Capital company in sports’ Club privileged position and the adopted Governance Model are significant factors in justifying the willingness of external shareholders to invest and be involved in this companies.